Factors associated with medication adherence in diabetes patients during the COVID-19 pandemic - Dinh, Tung Do; Phan, Linh Thuy Thi; Pham, Van Thuy Thi; Nguyen, Huong Thi Lien; Cao, Thao Thi Bich; Nguyen, Thao Thi; Nguyen, Son Tu; Nguyen, Dua Thi; Nguyen, Duy Huu; Nguyen, Linh Phuong; Tran, Toan Quoc; Thanh, Xuan Nguyen (Intelektual Pustaka Media Utama, 2025)
Identifying the factors affecting diabetes medication adherence is an important step in establishing interventions to improve prescription compliance and help patients manage their disease effectively and successfully. A cross-sectional study of patients with type 2 diabetes (T2D) at Saint Paul Hospital, Hanoi, Vietnam, used a structured questionnaire. Of the 250 patients, 60% (150) were female. The median age was 67.5 years, and the median duration of diabetes was 9.6 years. The mean medication adherence report scale (MARS-5) score was 23.1±3.1. The mean fear of COVID-19 (FCoVID-19) score was 16.8±6.3. The mean self-efficacy for appropriate medication uses scale (SEAMS) score indicating the patient’s confidence in taking medication correctly was 31.1±5.6. The mean medication literacy measure (MLM), which assesses the patient’s knowledge of diabetes medications, was 8.3±4.9, with 27.2% of patients having high levels. The relationships between adherence to medication and comorbidities, knowledge about medication, and psychological effects of diabetes were statistically significant according to multivariable linear regression. The study showed that intervention programs that focus on factors affecting adherence can be effective at improving patient health outcomes.